A Study of the Electron Regeneration Efficiency of Solar Cells Fabricated Using CMC/PVA-, Alginate-, and Xanthan-based Electrolytes - Shaafi, Nur Farha; Muzakir, Saifful Kamaluddin; Sahraoui, Bouchta (Makara Journal of Technology, 2019)
A photovoltaic (PV) mechanism consists of three important steps, i.e., (i) electron excitation upon absorption of photon with energy higher than the bandgap of fluorophore, (ii) excited-state electron injection from the fluorophore to the pho-toelectrode, and (iii) electron regeneration from the electrolyte to the fluorophore. An efficient electron regeneration could be achieved upon fulfillment of the requirements of energy alignment, i.e., lowest unoccupied molecular orbital of fluorophore (LUMOfluorophore) > redox potential of electrolyte > highest occupied molecular orbital of fluorophore (HOMOfluorophore). This study investigated the electron regeneration efficiency of excitonic solar cells fabricated using three polymer-based electrolytes, i.e., (i) 60% carboxymethyl cellulose (CMC) blended with 40% polyvinyl alcohol (PVA), (ii) alginate, and (iii) xanthan. The redox potentials of the electrolytes (Eo) were calculated using quantum chemical calculations under the framework of density functional theory. The compatibility of fluorophore and electro-lyte was analyzed in terms of the energy level alignment. The cells fabricated using the three polymer-based electrolytes were analyzed, with the CMC/PVA-based cell yielding the highest efficiency, η, of 1.39% under the illumination of the sun. The low η of the cells can be attributed to the incompatible Eo of the electrolytes, which exhibited a higher energy level than the LUMOfluorophore. The alginate- and xanthan-based cells exhibited inferior PV properties (i.e., open circuit voltage, short circuit current, fill factor, and η) to that of the CMC/PVA-based cell. This finding can be attributed to the increment of energy offset between Eo and HOMOfluorophore.